Complementary oligonucleotides regulate induced fit ligand binding in duplexed aptamers. Issue 3 (16th December 2016) - Munzar, Jeffrey D.; Ng, Andy; Corrado, Mario; Juncker, David
Abstract : Hybridizing a complementary oligonucleotide to an ATP aptamer is shown to functionally regulate a newly revealed induced fit ligand-binding pathway. Abstract : Duplexed aptamers (DAs) are engineered by hybridizing an aptamer-complementary element (ACE, e.g. a DNA oligonucleotide) to an aptamer; to date, ACEs have been presumed to sequester the aptamer into a non-binding duplex state, in line with a conformational selection-based model of ligand binding. Here, we uncover that DAs can actively bind a ligand from the duplex state through an ACE-regulated induced fit mechanism. Using a widely-studied ATP DNA aptamer and a solution-based equilibrium assay, DAs were found to exhibit affinities up to 1 000 000-fold higher than predicted by conformational selection alone, with different ACEs regulating the level of induced fit binding, as well as the cooperative allostery of the DA (Hill slope of 1.8 to 0.7). To validate these unexpected findings, we developed a non-equilibrium surface-based assay that only signals induced fit binding, and corroborated the results from the solution-based assay. Our findings indicate that ACEs regulate ATP DA ligand binding dynamics, opening new avenues for the study and design of ligand-responsive nucleic acids.